Postcolonialism, decoloniality and development - McEwan, Cheryl (Routledge perspectives on development., 2019)
Postcolonialism, Decoloniality and Development is a comprehensive revision of Postcolonialism and Development (2009) that explains, reviews and critically evaluates recent debates about postcolonial and decolonial approaches and their implications for development studies. By outlining contemporary theoretical debates and examining their implications for how the developing world is thought about, written about and engaged with in policy terms, this book unpacks the difficult, complex and important aspects of the relationships between postcolonial theory, decoloniality and development studies.